2013
DOI: 10.4141/cjps2013-326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commercial arbuscular mycorrhizal inoculants

Abstract: Afin d'optimiser l'usage des mycorhizes en agriculture, douze inoculants commerciaux de champignon mycorhizien arbusculaire (CMA) furent évalués en serres sur le maïs. Dans un premier temps, les inoculants furent propagés en pots sur sable stérilisé afin d'évaluer leur potentiel sur la colonisation racinaire du maïs par rapport à celui d'un sol agricole du Kenya et d'inventorier les espèces CMA contenues dans les inoculants. Trois inoculants augmentèrent le taux de colonisation racinaire comparé au sol agricol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 28 publications
3
53
0
2
Order By: Relevance
“…As a persistent and abundant generalist, A. colombiana may have been a good competitor under field conditions, as in the greenhouse. Moreover, since commercial inoculants can be either ineffective (Faye et al, 2013) or badly formulated (Corkidi et al, 2004), the use of A. colombiana is more likely to be affordable and effective for cassava farmers in tropical and subtropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…As a persistent and abundant generalist, A. colombiana may have been a good competitor under field conditions, as in the greenhouse. Moreover, since commercial inoculants can be either ineffective (Faye et al, 2013) or badly formulated (Corkidi et al, 2004), the use of A. colombiana is more likely to be affordable and effective for cassava farmers in tropical and subtropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Inocula containing one or more AM fungi are available commercially and are produced in a variety of ways (IJdo et al, 2011;Faye et al, 2013). Commercially-available inocula all require processing for the isolation of AM fungus propagules from the growth medium, formulation, and packaging for transport and sale.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that new developments should use renewable, non-contaminated natural resources opening up new avenues for research. Herrmann and Lesueur (2013) emphasized the importance of a suitable carrier to protect the microorganisms from the often-harsh conditions during storage and to ensure their survival and establishment after introduction into soils as well as the need for adequate quality controls, both during production and storage.…”
Section: Production Of the Biofertilizersmentioning
confidence: 99%
“…Faye et al (2013) assessed 12 commercial AMF inoculants sourced globally in a two-step experiment under greenhouse conditions. In this study, only three inoculants significantly increased root colonization levels compared to no sterile soil.…”
Section: Production Of the Biofertilizersmentioning
confidence: 99%
See 1 more Smart Citation